1956
DOI: 10.1111/j.1365-2621.1956.tb16909.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids in Peaches

Abstract: For greatest taste satisfaction from either fresh or processed peaches, the fruit must be picked and consumed as near to optimum maturity as possible. Flavor evaluation studies of canned cling peaches by Leonard, Luh, and Hinreiner (12) have shown that total titratable acidity in peaches decreases with maturation and that a fairly reliable indication of flavor rating is provided by the ratio of soluble solids to total acid in the raw fruit, when this value is referred to the total acidity. However, the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…1). This confirmed David et al (1956), Wills et al (1983a) and Chapman andHorvat (1990). However, Shenker andRieman (1953), Ryugo (1964), Ishida (1971), Souty and Andre (1975) and Meredith et al (1989) reported malic and citric acid were the only major organic acids in peaches.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…1). This confirmed David et al (1956), Wills et al (1983a) and Chapman andHorvat (1990). However, Shenker andRieman (1953), Ryugo (1964), Ishida (1971), Souty and Andre (1975) and Meredith et al (1989) reported malic and citric acid were the only major organic acids in peaches.…”
Section: Resultssupporting
confidence: 88%
“…Overall, 'Babygold 5' and 'Babygold 7' peaches rapidly increased in malic acid but very rapidly decreased in citric and quinic acid during ripening. A similar pattern was reported in 2 clingstone cultivars by David et al (1956). In an investigation of non-volatile acid changes in 'Monroe' peaches during fruit maturation (determined by capillary GC), Chapman and Horvat (1990) concluded that quinic was the major acid in immature fruits but rapidly decreased during maturation.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations